2012
DOI: 10.1177/1352458512459684
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal bands and cerebrospinal fluid markers in multiple sclerosis: associations with disease course and progression

Abstract: OCB positivity and elevated total CSF IgG and protein were moderately associated with a PPMS disease course, but not disease progression. Patients with atypical clinical presentations were more likely to have had CSF work-up, suggesting a testing bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 36 publications
2
36
1
1
Order By: Relevance
“…Some cases with a severe disease course may have been missed if they died soon after diagnosis but before they attended a BC MS clinic; this scenario is considered rare and the potential impact of such severe missed cases is likely to be minor. The vast majority of patients in the BC MS database are of Northern European descent; it is estimated that less than 5% of the cohort is of Asian, North American, Aboriginal or other ethnicity 37 38. These findings are therefore mostly generalisable to MS patients of Northern European descent; other ethnicities may experience different survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases with a severe disease course may have been missed if they died soon after diagnosis but before they attended a BC MS clinic; this scenario is considered rare and the potential impact of such severe missed cases is likely to be minor. The vast majority of patients in the BC MS database are of Northern European descent; it is estimated that less than 5% of the cohort is of Asian, North American, Aboriginal or other ethnicity 37 38. These findings are therefore mostly generalisable to MS patients of Northern European descent; other ethnicities may experience different survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Wurster reported 2 or 3 bands to be a "borderline" finding and used 4 bands as a cut-off value for definitely positive samples 16 . On the other hand, only 1 CSF-restricted band was considered sufficient for o-IgG positivity in another recent study 17 . We therefore decided to analyze o-IgG as well as ofLC in various disease groups and to compare the sensitivity and specificity of individual tests for MS and inflammatory nervous system diseases (IND) diagnosis in general.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques were standardized according to current recommendations and progress and are congruent with literature [11,23]. However, the subgroup analysis did not show significant results during the different studied periods whatever the technique used.…”
Section: Discussionmentioning
confidence: 54%
“…In a retrospective study of 143 MS patients followed for more than 5 years, the occurrence of secondary progression and increased EDSS during the follow-up period did not differ between OB positive and OB negative patients [18]. Recently, a study performed in 957 patients between 1982 and 2010 showed no significant differences between OB positive and negative patients in terms of the progression index and the proportion of patients reaching EDSS 6.0 within 10 years, in both PPMS and RRMS patients [23]. On the contrary, a worse prognosis in OB negative patients was reported in a study of 210 Turkish MS patients [24].…”
Section: Discussionmentioning
confidence: 92%